1987
DOI: 10.1159/000234459
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of C5a-Induced Bronchoconstriction in the Guinea Pig

Abstract: The effect of intravenous injection of C5a on pulmonary resistance and dynamic lung compliance was determined in anesthetized, artificially respirated guinea pigs. A mixture of C5a plus C5ades arg was purified from yeast-activated guinea pig serum and is referred to as C5a. Intravenous injection of C5a caused a dose-related bronchoconstriction as evidenced by a decrease in compliance and increase in resistance. Conversion of the C5a in the mixture to C5ades arg by carboxypeptidase B diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Pulmonary resistance and dynamic lung compliance were mea sured continuously in mechanically respirated, pentobarbitalanesthetized male guinea pigs (300-450 g. Dunkin-Hartley des cendants; Bio-Lab, St. Paul, Minn. USA) as described previously [10]. Results are expressed as the m ean±SE of the percentage of change from the control compliance or resistance before addition of the bronchoconstricting stimuli.…”
Section: Respiratory Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary resistance and dynamic lung compliance were mea sured continuously in mechanically respirated, pentobarbitalanesthetized male guinea pigs (300-450 g. Dunkin-Hartley des cendants; Bio-Lab, St. Paul, Minn. USA) as described previously [10]. Results are expressed as the m ean±SE of the percentage of change from the control compliance or resistance before addition of the bronchoconstricting stimuli.…”
Section: Respiratory Measurementsmentioning
confidence: 99%
“…Purification of guinea pig C5a utilized a modification of the method of Gerard and Hugli [13], as in our previously reported studies [10], The C5a used in these studies was a mixture of C5a plus C5adc, Arp, as verified by cellulose acetate electrophoresis.…”
Section: Purification O F Guinea Pig C5amentioning
confidence: 99%
See 1 more Smart Citation
“…Guinea pig C5a was purified as previously described [3], The material referred to as C5a throughout this paper is a mixture of C5a plus C5adcs.Arg. A spectrophotometric scan after cellulose ace tate electrophoresis indicated that C5a was approximately 26% of the C5a plus C5ades.Arg present.…”
Section: Purification O F Guinea Pig C5amentioning
confidence: 99%
“…Included among the bio logic activities of C5a is the ability to cause broncho constriction in the guinea pig [1][2][3] as well as to cause chemotaxis and aggregation of granulocytes [4], Pre vious studies by ourselves [3,5] and others [2,6] had suggested that histamine and cyclo-oxygenase prod ucts, but not leukotriene B4 or peptidoleukotrienes, play a major role in bronchoconstriction induced by intravenous administration of C5a. As an extension of the studies on mediators, the purpose of the present study was to determine if circulating white blood cells and platelets played a major role in the ability of in travenously injected C5a to cause bronchoconstric tion.…”
Section: Introductionmentioning
confidence: 99%